Gene therapy: medical treatment, eugenics or inheritanceõs hygiene? - Kohn Loncarica, Alfredo G.; Outomuro, Delia; Bortz, Jaime; Sánchez, Norma Isabel (Acta Bioethica, 2004)
The development of molecular genetics in the last two decades brought about important changes in the knowledge of physiopathology of the diseases, modifying the criteria for diagnosis and treatment and presenting the physician with new concepts originated from the continuously growing array of technological changes. The purpose of our paper is to present a fairly common bioethical standpoint about the gene therapy and, at the same time, to makesome critical remarks about this outlook, without failing to point out its contributions to the subject. In the first place, we present and discuss the definition of genetic illness proposed by Closer, Culver and Gert, its consequences and the standards we have to take into account when we have to decide to carry out a genetic diagnosis or not. Afterwards, we analyze the proposal of Berger in connection with the legitimation of genetic therapy. We conclude that the definition offered has an advantage: it is broad enough to include functional, psychological and even social alterations. However, it is strongly biologistic in that its criterion of what is normal is centered upon biological and statistical aspects, and it does not take into account the fact that the concept is culturally influenced. Also, in connection with theÊgene therapy, more than a moral objection, what the author proposes is a moratorium which rests on the inadequacy of the current knowledge and that it is based on an utilitarian philosophy. We sustain that it will be the community who will have to decide about until where it is willing to accept the "genetic lottery" and, in consequence, the reaches and the limits of the genomic medicine.